Customer Attributes Using the Services of Para-Banking Institutions - Mądra, Anna (Journal of Finance and Financial Law, 2014)
The goal of this article is present the customer attributes that uses the services of parabanking institutions. Using the results of the Financial Supervision Commission, which were provided by company TNS Pentor, as well as the results of a questionnaire survey defined the characteristics of a society that largely have an influence on the choice of institution providing loan and deposit services.